The Effect of Special Weight Exercises Using Auditory Apparatus According to Kinematic Indicators For Developing Auditory Response and Accuracy of Spiking in Volleyball - Yasir, Alaa Muhsun; Sikhe, Husein Sabhan (International Journal of Psychosocial Rehabilitation, 2020)
The research aimed at designing weight exercises using auditory apparatus according to kinematic  indicators for developing auditory response and the accuracy of spiking in volleyball as well as to identify  the effect of these exercises on the developing auditory response and the accuracy of spiking in volleyball  players. The subjects of the research were (12) volleyball players from the national center for gifted in  volleyball/ Ministry of Youth and Sports in Baghdad. Two setters as well as the libero were excluded making  total of (9) players as research subjects. The researchers used special weight exercises using auditory  apparatus according to some kinematic indicators for developing auditory response and spiking accuracy in  volleyball players. Kinovea was used for motor analyses to conclude the kinematical variables of spiking in  volleyball. Spiking accuracy test was conducted on volleyball players using auditory apparatus. The results  showed a great development in auditory response and spiking accuracy in the subjects understudy as well as  there was an improvement in some kinematical variables due to these exercises using the auditory apparatus  according to kinematical variables.